New metal based saturable absorber for ultrashort pulse generation / Muhammad Taufiq Ahmad - Muhammad Taufiq , Ahmad (2020)
Cost-efficient, robust and flexible laser systems are vital for a wide-range of applications ranging from high-precision material processing to biomedicine. This thesis aims to explore pure silver and gold based saturable absorbers (SAs) as Q-switcher and mode-locker in various fibre laser cavities. The generations of Q-switched pulses in 1-,1.55-, and 2-micron regions have been successfully demonstrated using a pure gold, which was deposited using electron beam deposition onto a PVA thin-film as SA. For instance, a stable Q-switched thulium-doped fibre laser (TDFL) operating at 1949 nm was successfully demonstrated with the gold SA. The proposed laser generates Q switched pulses with the maximum repetition rate of 21.95 kHz, the thinnest pulse width of 2.60 μs and the maximum pulse energy of 92.8 nJ. Passively Q-switched TDFL and erbium-doped fibre laser (EDFL) were also successfully demonstrated using a pure Ag thin-film, which was obtained using same technique and has 2% modulation depth. The silver-based Q-switched TDFL generates pulses at 28.33 kHz with pulse width of 4.82 μs and energy of 161.7 nJ at pump power of 498 mW. Passively Q-switched and mode locked EDFLs were also successfully achieved by utilizing D-shaped fibre deposited silver as SA. The generated Q-switched pulses exhibit maximum repetition rate of 66.74 kHz, the minimum pulse width of 6.12 μs and maximum pulse energy of 139.08 nJ which is comparable to other passively Q-switched EDFL system. The mode locked EDFL operates at 1.0 MHz repetition rate with 455 ns pulse width and pulse energy of 10.73 nJ. These findings show that pure gold and silver material have a great potential for photonic applications.